FOREIGN WORDS IN THE RUSSIAN LANGUAGE (Web of Teachers: Inderscience Research, 2025)
This article examines the process of borrowing foreign words into the Russian language, their impact on the development of vocabulary and perception by native speakers. The main sources of borrowings at various historical stages, as well as the role of foreign words in modern speech are analyzed. The opinions of famous writers and critics on the impact of borrowings on the language and culture are given. Special attention is paid to the adaptation of foreign words, their role in various spheres of life and possible consequences excessive enthusiasm for borrowings.